In vitro pulsatile flow study in compliant and rigid ascending aorta phantoms by stereo particle image velocimetry. (October 2021) - Yazdi, Sina G.; Docherty, Paul D.; Williamson, Petra N.; Jermy, Mark; Kabaliuk, Natalia; Khanafer, Adib; Geoghegan, Patrick H.
Highlights: Particle image velocimetry results demonstrated the necessity of compliance in any haemodynamic study. Introduction of compliance into the study of aorta haemodynamics demonstrated and increase in flow recirculation a direct correlation was made between the observed recirculation and high-risk areas for atherosclerosis Abstract: The aorta is a high risk region for cardiovascular disease (CVD). Haemodynamic patterns leading to CVD are not well established despite numerous experimental and numerical studies. Most overlook effects of arterial compliance and pulsatile flow. However, rigid wall assumptions can lead to overestimation of wall shear stress; a key CVD determinant. This work investigates the effect of compliance on aortic arch haemodynamics experiencing pulsatility. Rigid and compliant phantoms of the arch and brachiocephalic branch (BCA) were manufactured. Stereoscopic particle image velocimetry was used to observe velocity fields. Higher velocity magnitude was observed in the rigid BCA during acceleration. However, during deceleration, the compliant phantom experienced higher velocity. During deceleration, a low velocity region initiated and increased in size in the BCA of both phantoms with irregular shape in the compliant. At mid-deceleration, considerably larger recirculation was observed under compliance compared to rigid. Another recirculation region formed and increased in size on the inner wall of the arch in the compliant during late deceleration, but not rigid. The recirculation regions witnessed identify as high risk areas for atherosclerosis formation by a previous ex-vivo study. The results demonstrate necessity of compliance and pulsatility in haemodynamic studies to obtain highly relevant clinical outcomes.